ANALYSIS OF INTERNATIONAL REQUIREMENTS FOR DESIGNING OF CLINICAL TRIALS - O. S. Kobyakova; E. S. Kulikov; I. A. Deev; A. A. Dmitriev; N. A. Tabakaev; I. D. Pimenov; D. S. Tyufilin (Разработка и регистрация лекарственных средств, 2019)
During the analysis of international requirements for designing of clinical trials we found that principal documents are provided by ICH. The main standard in Russian Federation is the National State Standard “Good Clinical Practice”, that is similar to ICH GCP. Thorough industrial standards are issued by global regulators: FDA and EMA. Currently there is absence of local regulatory documents on designing clinical trials in Russia, thus there might be a distinct need in development of national regulatory documents and its harmonization with international standards for pharmaceutical industry.